REPRESENTASI CITRA PRINCESS DALAM IKLAN “DREAM BIG, PRINCESS” (Analisis Semiotika Charles Sanders Peirce ) - Juliano Richi (Jurnal Visi Komunikasi, 2020)
A Princess is a title possessed by a female figure in a leadership court of a nation with a Monarch system in its government, however these days, the figure of a Princess tend to be portrayed incorrectly in various media resulting a construction of fallacy in the society’s point of view towards it. As an effort to deconstructs the fallacy built in the society referring to the Princess figure by employing its successful franchise of the Disney Princess, Disney attempts to instill an early educational message regarding the value of feminism and gender equality towards children globally by utilizing a campaign known as ‘Dream Big, Princess’ referring to the cause and delivering the message through commercials which one of them was specifically published as the ‘Where Will Your Imagination Take You?’ version. Done by applicating the constructivism paradigm, this research was intented to find the commercial way of utilizing various sign to representate an ideal image of the Princess’ figure as a role model. By adopting the qualitative methods and the viewpoint of Charles Sanders Peirce’s Semiotic theory, this research was done to the main analysis unit consisting of 11 different sequences from the commercial itself. By the end of the research, signs implying inclusivity, exploration, determination, creation, potential, braveness and feminism shows and as a whole, resulting how a Princess tend to be constructed more of an inspirative figure in the eyes of children which their presence as a role model is able to motivate children with various backgrounds to realize their full potential in their way of reaching their own hopes and dreams.